PENGARUH KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN TAHAPAN KASTOLAN TERHADAP HASIL BELAJAR - Stephanie, Erviana Nadia; Muzadi, Alfa Ridzi Misbaqul Khoirun; Budiman, Muhammad (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The research in this article aims to find out whether there is an influence of students errors in solving math word problems on learning outcomes. The number of samples used was 32 students of class 5 MIN 2 Bengkulu city. The variables studied were student errors and learning outcomes. This article uses quantitative research method. Where to use the regression test, correlation, normality and linearity. Samples were taken randomly Researchers used survey research methods. After being given test questions and calculating the percentage, there are several results obtained, namely conceptual errors in students are 15,6%, procedural errors are 43,8%, and technical errors of 40,6%. So the most errors made are procedural errors. After using the normality, linearity and regression tests, it can be cocluded that sig value.Regresion (0,000) (0,025) indicates that student errors have a significant effect on learning outcomes. The R square number is 0,798 this indicates that the student’s error test score has an effect of 79,8% on learning outcomes and the remaining 20,2% is influenced by variables not examined.